Avaliação do potencial do maracujá da Caatinga (Passiflora cincinnata Mast.) na elaboração de bebidas alcoólicas fermentadas - Santos, Renata Torres dos Santos e (2023)
The high Brazilian production of different tropical fruit varieties is the third largest in the world. However, there are still many native and exotic fruits that have not been economically exploited. In this scenario, the Caatinga passion fruit (Passiflora cincinnata Mast.), which is a native fruit of the semi-arid region of the Brasilian Northeast, is considered of great economic importance for the strengthening of family farming and the regional development of the semi-arid Northeastern population, which harvests the fruits and sells them for consumption in natura, or in the form of pulp, jellies, sweets, ice cream and liqueur. It is a climatic fruit and when ripe, it has a greenish-yellow color, whitish to sterile rind, ex-ripe flavor, soluble solids content of 8 to 13%, pH in the range of 2.0 to 3.0 and 3.0 and pH in the range of 2.0 to 3.0 and titratable acidity of approximately 3.0%. From this, considering what has properties for the processing of resulting beverages, this study to proposed evaluate the potential of passion fruit from the Caatinga for the production of fermented alcoholic beverages, especially in the elaboration of carbonated alcoholic fermented (sparkling) dry and sweet, evaluating the beverage quality and sensory quality by consumers. The fermented were made from the fermentation of passion fruit must from the Caatinga, chaptalized with sucrose, by the action of Saccharomyces cerevisiae yeasts and showed approximate efficiency of 89%, production of 0.71 g L-1 h-1, product yield (YP/S) of 0.453 and product and substrate formation rates, rp and rs, of 1.57 and 0.71 g L-1 h-1, respectively. With the exception of total acidity, the results obtained, for the quality standard, in accordance with the limits established by Brazilian legislation, and the quality of the beverage obtained showed the existence of a wide variety of bioactive compounds present. Twenty-two phenolic compounds were indentified (phenolic acids, flavonols, flavanols and stilbenes) and the relevant antioxidant activity was considered. The sensory score obtained was considered satisfactory. It is concluded that Passiflora cincinnata Mast. presents promising potential in the elaboration of gasified alcoholic fermented (sparkling wine).